Catch Composition of Portunus pelagicus from Different Fishing Gear Used along Palk Bay Water of Ramanathapuram Coast of Tamil Nadu, India - Vaishnav, Anand; Neethiselvan, N.; Ravikumar, T.; Lal, Jham; Kumar, Shailendra; Jayaswal, Rajesh; Kashyap, Narsingh; Ramasre, Jaiswar Rahul (International Journal of Bio-resource and Stress Management, 2024)
The experiment was conducted during November, 2019 to October, 2020 at Palk Bay water of Ramanathapuram coast of Tamil Nadu to investigate the catch composition of P. pelagicus, commonly known as the blue swimming crab, focusing on different fishing gears used in the Palk Bay waters. 25 fishing grounds were identified within 1 to 5 nautical miles, where bottom-set gillnets, trammel nets, and country trawls were employed by fishermen. Craft types included non-motorised small wooden boats and FRP boats with outboard motor engines ranging from 9.9 to 20 horsepower. Bottom-set gillnets, with mesh sizes of 80 to 100 mm, were primarily used to target crabs, while trammel nets and country trawls were utilised for cephalopods and as bycatch. The study discovered a diverse size range of captured P. pelagicus, with carapace lengths ranging from 30 to 92 mm and carapace widths spanning from 70 to 193 mm. Notably, individuals within the length group of 55 to 60 mm and the width group of 115 to 125 mm constituted the predominant size classes. Catch per unit effort analysis revealed fluctuations across gear types, with bottom-set gillnets contributing the majority (94.8%) of the total catch, followed by trammel nets (3.19%) and country trawls (2.01%). Comparison with previous studies highlighted the historical dominance of bottom-set gillnets in P. pelagicus fisheries while emphasising the complementary contributions of trammel nets and country trawls. These findings underscored the importance of integrated management approaches to sustainably manage crab fisheries in the region.